Humoral response to anti-COVID immunization and SARS-CoV-2 infection in HIV-infected persons - Marić, Daniela; Andrić, Vanja; Brkić, Snežana; Zuvić, Dragana; Mijović, Romana; Bulović, Aleksandra (Vojnosanitetski pregled, 2025)
Background/Aim. At the beginning of the coronavirus disease 2019 (COVID-19) pandemic, human immunodeficiency virus (HIV)-infected persons (HIP) were considered to be at an increased risk of more severe forms of the disease. Although vaccination of HIP is deemed essential, data on the humoral response to both infection and vaccination in this population are inconsistent, particularly when comparing different vaccine types. The aim of this study was to examine factors that could influence severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) anti-spike protein antibody titers in HIP after vaccination and/or exposure to the virus. Methods. The study included all HIP who came for routine check-ups to the Center for HIV/AIDS of the University Clinical Center of Vojvodina, Serbia, from April to December 2022 and who had received at least two doses of the vaccine or had a positive history of COVID-19. Data on age, duration of antiretroviral therapy (ART), nadir and current CD4+ and CD8+ T-cell counts, and type of vaccine were collected from medical records and the national database. Immunoglobulin G (IgG) antibodies against SARS-CoV-2 spike protein were determined in the sera of HIP using the AdviseDx SARS-CoV-2 IgG II assay. Results. The research included 226 HIP with undetectable viremia, in 96.3% of cases, the CD4 T-lymphocyte count was over 350 cells/mm3. Out of 171 HIP who received at least two doses of a vaccine, 64 (37.4%) were both vaccinated and had COVID-19 and 107 (62.6%) were vaccinated and had no evidence of COVID-19. Among the vaccinated participants, 62% received three doses and 38% received two vaccine doses. Regarding the type of vaccine, 59.6% of participants received a messenger ribonucleic acid (mRNA) vaccine, 25.1% an inactivated vaccine, and 15.3% received a vector vaccine. A better humoral response was observed in the mRNA compared to the inactivated vaccines and in three compared to two doses in the case of mRNA vaccines. Age and duration of ART negatively correlated with antibody titers, while the number of CD8 T-cells had a positive correlation. Conclusion. The study showed the immunogenicity and safety of full vaccination against COVID-19 in HIP with any of the available vaccines.